The AS‐RBM15 lncRNA enhances RBM15 protein translation during megakaryocyte differentiation. (26th April 2016) - Tran, Ngoc‐Tung; Su, Hairui; Khodadadi‐Jamayran, Alireza; Lin, Shan; Zhang, Li; Zhou, Dewang; Pawlik, Kevin M; Townes, Tim M; Chen, Yabing; Mulloy, James C; Zhao, Xinyang
Abstract: Antisense RNAs regulate the transcription and translation of the corresponding sense genes. Here, we report that an antisense RNA, AS‐RBM15, is transcribed in the opposite direction within exon 1 of RBM15 . RBM15 is a regulator of megakaryocyte (MK) differentiation and is also involved in a chromosome translocation t(1;22) in acute megakaryocytic leukemia. MK terminal differentiation is enhanced by up‐regulation of AS‐RBM15 expression and attenuated by AS‐RBM15 knockdown. At the molecular level, AS‐RBM15 enhances RBM15 protein translation in a CAP‐dependent manner. The region of the antisense AS‐RBM15 RNA, which overlaps with the 5′UTR of RBM15, is sufficient for the up‐regulation of RBM15 protein translation. In addition, we find that transcription of both RBM15 and AS‐RBM15 is activated by the transcription factor RUNX1 and repressed by RUNX1‐ETO, a leukemic fusion protein. Therefore, AS‐RBM15 is a regulator of megakaryocyte differentiation and may play a regulatory role in leukemogenesis. Synopsis: The lncRNA AS‐RBM15 is transcriptionally up‐regulated by RUNX1 and enhances RBM15 protein translation via its overlapping region with the RBM15 5′UTR. AS‐RBM15 activated by the transcription factor RUNX1 promotes megakaryocyte differentiation via enhancing RBM15 protein translation. Exon 1 of AS‐RBM15, which overlaps with the 5′UTR of RBM15 mRNA, is sufficient to enhance 5′cap‐dependent RBM15 protein translation. The cytoplasmic fraction of AS‐RBM15 is increased in response to megakaryocyte differentiation signals. Abstract : The lncRNA AS‐RBM15 is transcriptionally upregulated by RUNX1 and enhances RBM15 protein translation via its overlapping region with the RBM15 5′UTR.